APLIKASI INTEGRASI INTERKONEKSI KEILMUAN DI LEMBAGA PENDIDIKAN TINGGI - Eka Saftri; Ihsan Sa’dudin (Tadrib: Jurnal Pendidikan Agama Islam, 2019)
This paper reveals that the unification between various kinds of science is very important for scientific development itself. The union between the science of religion and science is a new breakthrough for existing science. However, the application is still lacking in a more productive domain. UIN Sunan Kalijaga Yogyakarta is a pioneer of Educational Institutions that implement integration and interconnection in their environment. There are various kinds that can be seen, namely the curriculum, teaching staff and even the building. The existence of openness between one knowledge and another makes it a continuous flow of knowledge and influence between one another. Therefore, applying scientific integration and interconnection needs to be applied in other educational institutions in both higher education institutions and primary, secondary and upper education institutions to formal and non-formal educational institutions. This aims to dismantle the wall of scientific dichotomy which still shackles existing scientific developments. The concept of integration-interconnection is illustrated in the "Theoantropocentric-Integralistic Spider Web of Science in State Universities" which is often called a web spider. The purpose of the web spider is essentially the inter-knowledge between one and the other interlocking (integration-interconnection). The ethos and breath of the scientific epistemology reintegration of the UIN era were developed, there are three things, including Hadarah al-Nash (buffer of Bayani text culture), Hadarah al-lmIlm (technique, communication) and Hadarah al-Falsafah (ethics). The three breaths are used as a reference for the UIN scientific field and a foothold in developing it.